Using SMT solver and symbolic execution to generate test inputs for C programs : Luận văn ThS. Công nghệ thông tin - Do, Quoc Huy (ĐHCN, 2017)
Chapter 1: Introduction. Chapter 2: CREST. Chapter 3: realCREST: A new test generation tool based on CREST. Chapter 4: Experiment and discusion. Chapter 5: Conclusion and Future Work.